DENSIDADE E RENDIMENTO DE GRÃOS EM CANOLA - kruger, Cleusa a. M. B.; Silva, Jose A. G. D.; Medeiros, Luis P.; Silva, Adair J. d.; Martins, João A. K.; Wagner, Furhmann; Valentini, Ana P. F.; Zambonato, Felipe; Gaviraghi, Fernando (Salão do Conhecimento, 2013)
Resumo